Teaching Recount Text Using TED Talks Video to Enhance Students’ Speaking Skill at the Secondary School - Dira Savira; Iwan Fauzi (Pusat Kajian Bahasa Daerah & Budaya, 2023)
Speaking is one of the basic skill skills in English language learning in addition to reading, speaking, and listening. Speaking skill is needed to help students to communicate and socialize with other people. This study is to find out the effect of teaching recount text using TED Talks Video on students’ speaking skill at the secondary school. Pre-experimental research with one group pre-test and post-test design was used in this study. The subjects were taken from the eleventh graders of secondary school in Kalimantan Tengah by using purposive sampling. The subjects were taught to speak personal recount texts using TED Talks Video. The instrument used to collect the data was the oral test to each student. The result showed that there is a significant effect of teaching recount text using TED Talks Video on students’ speaking skill at the secondary school.